Endogenous distribution, politics, and growth - Satya Prasanna Das; Chetan Ghate (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper generalizes the analysis of distributive con?ict, politics, and growth developed by by Alesina-Rodrik (1994). We construct a heterogenous-agent framework in which both growth and the distribution of wealth are endogenous. Due to adjustments in the distribution of wealth, the composition of factor ownership across households equalizes in the long run. This implies that the optimal tax rate is the same for all households and equals the growth maximizing tax rate. Hence, there is no distributive con?ict in the long run. When the model is augmented with a non-political redistributive policy, the model predicts that long run growth exhibits a negative monotonic relationship with respect to this policy, i.e., a redistributive policy that leads to a more equitable wealth distribution unambiguously reduces growth in the long run.
Keywords: E62; D31; P16; O40; 330; Median Voter; Endogenous Growth; Wealth Distribution; Distributive Conflict; Redistributive Policy; Einkommensverteilung; Verteilungstheorie; Optimale Besteuerung; Neue Wachstumstheorie; Einkommensumverteilung; Median Voter; Theorie